A Performance Analysis of Public Expenditure on Maternal Health in Mexico. - Edson Servan-Mori; Leticia Avila-Burgos; Gustavo Nigenda; Rafael Lozano (PLoS ONE, 2016)
We explore the relationship between public expenditure, coverage of adequate ANC (including timing, frequent and content), and the maternal mortality ratio--adjusted by coverage of adequate ANC--observed in Mexico in 2012 at the State level. Additionally, we examine the inequalities and concentration of public expenditure between populations with and without Social Security. Results suggest that in the 2003-2011 period, the public expenditure gap between women with and without Social Security decreased 74%, however, the distribution is less equitable among women without Social Security, across the States. Despite high levels of coverage on each dimension of ANC explored, coverage of adequate ANC was lower among Social Security than non-Social Security women. This variability results in differences up to 1.5 times in State-adjusted maternal mortality rate at the same level of expense and maternal mortality rate, respectively. The increase in the economic resources is only a necessary condition for achieving improved health outcomes. Providing adequate health services and achieving efficient, effective and transparent use of resources in health, are critical elements for health systems performance. The attainment of universal effective coverage of maternal health and reducing maternal mortality in Mexico, requires the adjustment of policy innovations including the rules of allocation and execution of health resources. Health policies should be designed on a more holistic view promoting a balance between accessibility, effective implementation and rigorous stewardship.